Evidencia científica del duelo del profesional en equipo de enfermería ante la muerte del paciente en ambiente hospitalario: una revisión integradora (Research, Society and Development, 2022)
Objective: To analyze the scientific literature produced on the grief of the nursing professional in the face of inpatient death. Method: An integrative literature review performed through consultation in the following databases: Pubmed, Scielo, Lilacs, Cinahl, Scopus and Web of Science databases. The search was guided by the question: What are the scientific evidences of the grief of the nursing in the face of the inpatient's death?? The search for scientific articles was carried out in August and September 2020, including articles from 2015 to 2020. Results: Eight articles with different methodological designs were selected. A feeling of grief was reported by the nursing professional in the face of the death of their patient, its consequences and coping mechanisms. Conclusion: The grief of the nursing professional in the face of the patient's death was described and presented varied consequences, the need for greater professional training was reported, as well as the need for more studies on the subject, to assess the various aspects of its causes, consequences and coping mechanisms.